Business Strategy Recommendation for Bank Pulsa Indonesia (BPI) - Aryo Indra Djati, SE., MBA (Management and Leadership Study Programme, 2018)
The fastest growth of business or industry in the world is technology; because the uses of technology makes people live become more effective and efficient. The technology based industry almost scope every sector of business include financial sector, One of the financial activities that effected by the development of the technology is the payment instruments. by the fast growth of technology and the use of Smartphone comes up the next generation of the payment instrument which is cardless (without physical card) and no more need ATM machine where people can do their financial transaction through their mobile phone and it is called Digital Money or it most popular in society with the name E-wallet; in a simple understanding it is mean digitalize the money.The Digital Money is expected to replace cash because the use of this new instrument much more effective, efficient and save. In Indonesia Digital financial service or digital payment technology becomes one of the concentrations to be explored by many business institutions in the last years such as Banks and telecommunication providers in order to provide the easiest way to access or to use the daily financial needs of people trough their Smartphone, it could be website-based (internet banking) or mobile apps (mobile banking, Rekening poncel, T-Cash, etc). By the very huge and fresh market that can be explored from the digital financial services the players or the actors of this business sector is not only the big business institution but also the Startups. More over the government highly support to increase the use of digital money not only for medium and high level of society but also the lower class of society and SME’s, the concrete support to trigger the development of digital money the government through Central Bank of Indonesia simplify the licensing for digital money provider, That is way there are many startups that focusing on developing and providing the digital money in Indonesia, one of them is Bank Pulsa Indonesia.Bank Pulsa Indonesia (BPI) as a new comers choose Larangan Tangerang as their initial target market to launch the services, because the structure of demography and economy of Larangan Tangerang is suitable with strategy of BPI which is serving lower class of society and SME’s. As new comers Bank Pulsa Indonesia (BPI) face some challenges, the services that BPI offer to the market are new things for them and BPI need to educate the market that the services of BPI is solution for their daily financial transaction. So that BPI should have strategy in order to be received in the market. Research in this Journal is set base on unclear business strategy of BPI. Shareholders is not pay attention about business strategy as a new player at the Financial Technology market. BPI needs to make new marketing strategy effectively by assessing the external and internal environmental situation, the current strategy, the current 7Ps of marketing mix, and considering for direct competition. The result would to achieve is the effective and focused recommendation business strategy at the end of2this Journal. This research analyze the external factor of digital financial industry and internal factor of Bank Pulsa Indonesia as a start up in digital financial industry using SWOT analysis. The objective of this research is to provide business strategy recommendation for Bank Pulsa Indonesia along with implementation plan for short term and long term period.